Brazilian dentists' perception of dentin hypersensitivity management - Livia Fávaro Zeola; Daniela Navarro Ribeiro Teixeira; Alexia da Mata Galvão; Paola Gomes Souza; Paulo Vinícius Soares (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract: The aim of this study was to investigate how Brazilian dentists perceive and manage dentin hypersensitivity (DH) in their clinical routine. A 13-item questionnaire-based survey was developed and sent electronically to a convenience sample of dentists. The questionnaire assessed the personal and dental practice characteristics of the sample, the occurrence of DH in their daily clinical practice, and management strategies. The data were analyzed descriptively and together with the chi-square test (a = 0.05). A total of 353 responses were obtained from September 2017 to March 2018. Of all the respondents, 62% were females, 49.9% reported fewer than five years of dental practice, and 70.5% were self-identified as private practitioners. Most of the dentists reported an estimated frequency (30-60%) of patients with DH in their practice. The most frequently cited (91.79%) trigger of DH was air blast and/or scratching with a probe. The first-choice strategy to manage DH was a dentin desensitizer (48.16%). The number of years in clinical practice did not influence DH relapse frequency (p = 0.76) significantly, or consider DH treatment as a problem (p = 0.22). The present findings indicate that, regardless of clinical experience, dentists in Brazil still consider DH management a challenge in their daily dental practice. In addition, the results suggest that guidelines should be developed to disseminate the available knowledge regarding this condition in ways that may influence decision-making processes among practitioners.